'We have long memories in this area': Ulster Defence Regiment place-memory along the Irish border. (October 2022) - Robinson, Joseph S
A large body of literature assumes post-conflict societies can and should mediate public memory towards frames conducive to a reconciled future. However, this article argues that such a drive marginalises survivors of political violence who narrate the past as still-present wounds. The linear temporality of transitional justice presumes an idealised trajectory through time, away from violence and towards reconciliation. However, this idealised temporality renders anachronistic survivors who depend on the prolongation of traumatic pasts for the possibility of political change. Using the case of former Ulster Defence Regiment in Northern Ireland, this article examines this prolongation through the lens of Ulster Defence Regiment survivors' resistant place-memory along the Southwest run of the Irish border. Through the performative retemporalisation of everyday places and landscapes, survivors demand that their resistant memories and narrative frames of past violence still belong and still have active political resonance in transitional political space.